2016
DOI: 10.17795/modernc.9456
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Seroprevalence of Hepatitis E Among Blood Donors Referring to Blood Donation Centers in Birjand County in Iran

Abstract: Background: Hepatitis E is among the most important health challenges in many countries. This study aimed at investigating the sero-prevalence of hepatitis E among blood donors in Birjand county, Iran. Methods: This cross-sectional descriptive-analytical study was performed in 2013 -2014 on 340 blood donors who referred to blood donation centers in Birjand county, Iran, for blood donation. The participants were recruited through simple random sampling. A researcher-made questionnaire was used for data collecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
2
2
0
Order By: Relevance
“…Results of this study showed that a positive serology of HEV was lower in educated people, which conforms to the results of the previous studies in Iran (6,8,10). Positive serology in people with primary education was 3.87 compared to people with an academic education.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Results of this study showed that a positive serology of HEV was lower in educated people, which conforms to the results of the previous studies in Iran (6,8,10). Positive serology in people with primary education was 3.87 compared to people with an academic education.…”
Section: Discussionsupporting
confidence: 92%
“…In the majority of the studies, no relation was established between age and prevalence of the disease, which is similar to the current study (3,6,8,10). Results of this study showed that a positive serology of HEV was lower in educated people, which conforms to the results of the previous studies in Iran (6,8,10).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…HEV-IgM was positive in 10 (5%) donors, and HEV-RNA was detected in 6 (3%) cases of the blood donors. The incidence of HEV viremia in European studies ranges from 1:600 to 1:15000 [28,34,35], and several studies have documented HEV blood transfusion transmission [34,36,37]. The genotype of HEV was genotype 1.…”
Section: Positive Heviggmentioning
confidence: 99%